2016
DOI: 10.1007/s12325-016-0306-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nuclear Receptors in the Pathophysiology, Natural Course, and Drug Treatment of NAFLD in Humans

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 256 publications
1
46
0
1
Order By: Relevance
“…The peroxisome proliferator-activated receptors- (PPAR-) alpha and delta are transcription factors finely regulating energetic fluxes and metabolic pathways [38]. PPAR- α is highly expressed in liver and regulates the rates of fatty acid catabolism and lipogenesis in response to nutritional demands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peroxisome proliferator-activated receptors- (PPAR-) alpha and delta are transcription factors finely regulating energetic fluxes and metabolic pathways [38]. PPAR- α is highly expressed in liver and regulates the rates of fatty acid catabolism and lipogenesis in response to nutritional demands.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR- δ is constitutively expressed and regulates β -oxidation in muscle. In the liver, it controls hepatic glucose and lipoprotein metabolism and exerts anti-inflammatory effects [38, 43]. Beneficial effects of PPAR- δ agonists on improvement of hepatic steatosis and inflammation have been reported in mouse models of NASH [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have demonstrated that simple steatosis can progress to NASH and that both conditions progress to advanced fibrosis, though this occurs at a much slower pace for simple steatosis than for NASH[16,25-27]. The severity of hepatic fibrosis, rather than NASH, largely dictates the prognosis of liver-related outcomes in NAFLD[21,28,29]. …”
Section: Nafldmentioning
confidence: 99%
“…Risk factors of NAFLD and NASH include type 2 DM, central obesity, hypertension, dyslipidaemia, lack of sleep and physical inactivity . More recently, it has been proposed that dysregulation of nuclear receptors such as peroxisome proliferator‐activated receptors, liver X receptors and farnesoid X receptors, which are transcriptional factors that regulate several metabolic pathways, plays a significant role in the development and progression of NAFLD …”
Section: Introductionmentioning
confidence: 99%